[μ-1,4-Bis(diphenyl-phosphino-yl)butane-κO:O']bis-[cyclo-pentyl-diphen-yl(trifluoro-acetato-κO)tin(IV)]. - Teo, Y.Y.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The mol-ecule of the dinuclear title compound, [Sn(2)(C(5)H(9))(2)(C(6)H(5))(4)(C(2)F(3)O(2))(2)(C(28)H(28)O(2)P(2))], lies on a center of inversion at the mid-point of the central C-C bond of the bridging phosphine oxide ligand. The Sn atom is five-coordinate in a trans-C(3)SnO(2) trigonal-bipyramidal geometry.